Pharmacokinetics and Pharmacodynamics of Remimazolam (CNS 7056) after Continuous Infusion in Healthy Male Volunteers Part II. Pharmacodynamics of Electroencephalogram Effects - Eisenried, Andreas; Schüttler, Jürgen; Lerch, Marco; Ihmsen, Harald; Jeleazcov, Christian (Anesthesiology, 2020)
Background:Remimazolam (CNS 7056) is a new ultra-short acting benzodiazepine for IV sedation. This study aimed to investigate the electroencephalogram (EEG) pharmacodynamics of remimazolam infusion.Methods:Twenty healthy male volunteers received remimazolam as continuous IV infusion of 5 mg/min for 5 min, 3 mg/min for the next 15 min, and 1 mg/min for further 15 min. Continuous EEG monitoring was performed by a neurophysiologic system with electrodes placed at F3, F4, C3, C4, O1, O2, Cz, and Fp1 (10/20 system) and using the Narcotrend Index. Sedation was assessed clinically by using the Modified Observer's Assessment of Alertness and Sedation scale. Pharmacodynamic models were developed for selected EEG variables and Narcotrend Index.Results:EEG changes during remimazolam infusion were characterized by an initial increase in beta frequency band and a late increase in delta frequency band. The EEG beta ratio showed a prediction probability of Modified Observer's Assessment of Alertness and Sedation score of 0.79, and could be modeled successfully using a standard sigmoid E-max model. Narcotrend Index showed a prediction probability of Modified Observer's Assessment of Alertness and Sedation score of 0.74. The time course of Narcotrend Index was described by an extended sigmoid E-max model with two sigmoid terms and different plasma-effect equilibration times.Conclusions:Beta ratio was identified as a suitable EEG variable for monitoring remimazolam sedation. Narcotrend Index appeared less suitable than the beta ratio for monitoring the sedative effect if remimazolam is administered alone.

Pharmacokinetics and Pharmacodynamics of Remimazolam (CNS 7056) after Continuous Infusion in Healthy Male Volunteers: Part I. Pharmacokinetics and Clinical Pharmacodynamics - Schüttler, Jürgen; Eisenried, Andreas; Lerch, Marco; Fechner, Jörg; Jeleazcov, Christian; Ihmsen, Harald (Anesthesiology, 2020)
BACKGROUND: Remimazolam (CNS 7056) is a new ultra-short-acting benzodiazepine for intravenous sedation and anesthesia. Its pharmacokinetics and pharmacodynamics have been reported for bolus administration. This study aimed to investigate the pharmacokinetics and pharmacodynamics of remimazolam after continuous infusion. METHODS: Twenty healthy male volunteers (20 to 38 yr, 64 to 99 kg) received remimazolam as continuous intravenous infusion of 5 mg/min for 5 min, 3 mg/min for the next 15 min, and 1 mg/min for further 15 min. Pharmacokinetics of remimazolam and its metabolite were determined from arterial plasma concentrations. Sedation was assessed using the Modified Observer's Assessment of Alertness and Sedation scale. Pharmacokinetic-pharmacodynamic modeling was performed by population analysis. Hemodynamics and the electrocardiogram were also investigated. RESULTS: Pharmacokinetics was best described by a three-compartment model for remimazolam and a two-compartment model with transit compartment for the metabolite. Remimazolam showed a high clearance (1.15 ± 0.12 l/min, mean ± SD), a small steady-state volume of distribution (35.4 ± 4.2 l) and a short terminal half-life (70 ± 10 min). The simulated context-sensitive halftime after an infusion of 4 h was 6.8 ± 2.4 min. Loss of consciousness was observed 5 ± 1 min after start, and full alertness was regained 19 ± 7 min after stop of infusion. Pharmacodynamics of Modified Observer's Assessment of Alertness and Sedation score was best described by a sigmoid probability model with effect site compartment. The half-maximum effect site concentration for a Modified Observer's Assessment of Alertness and Sedation score less than or equal to 1 was 695 ± 239 ng/ml. The equilibration half-time between central and effect compartment was 2.7 ± 0.6 min. Mean arterial blood pressure decreased by 24 ± 6%, and heart rate increased by 28 ± 15%. Spontaneous breathing was maintained throughout the study. There was no significant prolongation of the QT interval of the electrocardiogram observed. CONCLUSIONS: Remimazolam was characterized by a pharmacokinetic-pharmacodynamic profile with fast onset, fast recovery, and moderate hemodynamic side effects.
CRIS-Team Scopus Importer:2020-03-27